Willingness to Pay for the Pedestrian Crossing Management to the Elderly in Bangkok - Bejranonda, Somskaow; Lim, Aunkung (Journal of Business, Innovation and Sustainability (JBIS), 2022)
Pedestrian crossing in the city is essential for the elderly, especially when Thailand becomes an aging society. This paper aimed at 1) investigating the behavior and opinion to use the pedestrian crossings of people in Bangkok and 2) evaluating the benefits obtained from the appropriate pedestrian crossings management for the elderly in Bangkok by applying contingent valuation method (CVM). It was found that most respondents use the pedestrian overpass rather than the jaywalking. They agreed that the jaywalking was not appropriate for the elderly because there were no traffic lights at the jaywalking. The average value of WTP for the arrangement of the proper pedestrian crossings in Bangkok for the elderly was equal to 1,396 baht/person/year. Therefore, the benefits obtained from the pedestrian crossings for the elderly in Bangkok in 2020 was at approximately 5,600 million baht/year.